Spinal nerve injury causes upregulation of ErbB2 and ErbB3 receptors in rat dorsal root ganglia - Mizobuchi, Satoshi (Dove Medical Press, 2013)
It is generally known that peripheral nerve injury causes changes in expression of some growth factors in the dorsal root ganglion. Altered expression of ErbB receptors, a well-known growth factor in somatic cells, reportedly follows peripheral nerve injury in the spinal dorsal horn; however, it remains unknown whether the expression of these receptors is altered in the dorsal root ganglion after nerve injury. Therefore, this study examined the gene expression profiles of ErbB receptors in bilateral lumbar (L)4/L5 dorsal root ganglia, using L5-selective spinal nerve ligation in model rats as a peripheral nerve injury model. The expression of ErbB2 and ErbB3 was observed in the dorsal root ganglia of the mature rat, despite ErbB1 and ErbB4 showing only subtle expression. We also demonstrated that peripheral nerve injury induced significant increases in ErbB2 and ErbB3 in the ipsilateral dorsal root ganglion as compared with uninjured nerve. Expression changes in ErbB receptors appear to play important roles in nerve injury and subsequent nerve regeneration.